Magnetic Fe3O4-Reduced Graphene Oxide Nanocomposites-Based Electrochemical Biosensing - Yu, Lili; Wu, Hui; Wu, Beina; Wang, Ziyi; Cao, Hongmei; Fu, Congying; Jia, Nengqin (Nano-Micro Letters, 2014)
An electrochemical biosensing platform was developed based on glucose oxidase (GOx)/Fe3O4- reduced graphene oxide (Fe3O4-RGO) nanosheets loaded on the magnetic glassy carbon electrode (MGCE). With the advantages of the magnetism, conductivity and biocompatibility of the Fe3O4-RGO nanosheets, the nanocomposites could be facilely adhered to the electrode surface by magnetically controllable assembling and beneficial to achieve the direct redox reactions and electrocatalytic behaviors of GOx immobilized into the nanocomposites. The biosensor exhibited good electrocatalytic activity, high sensitivity and stability. The current response is linear over glucose concentration ranging from 0.05 to 1.5 mM with a low detection limit of 0.15 μM. Meanwhile, validation of the applicability of the biosensor was carried out by determining glucose in serum samples. The proposed protocol is simple, inexpensive and convenient, which shows great potential in biosensing application.